Development of Learning Module of Lampung Ship ornament for Students - Ismayan Dwiprayoga; I Ketut Sunarya (Newinera Publisher, 2026)
The aim of this study was to determine the understanding of vocational students using the learning module of Lampung ship ornaments. This research uses the development method or Research and Development adopted from Borg and Gall. The stages of this research include needs analysis, planning, initial product development, initial field test, revision of test results, main product field test, product revision, results of learning modules. The subjects in this study were vocational students totaling 28 students consisting of 7 students for the limited feasibility test, and 21 students for the field trial. The data were collected through validation sheets, creativity questionnaires, and learning outcomes. The results of this study are as follows. (1) The learning module of Lampung ship ornaments is declared feasible to improve understanding for vocational students. (2) The learning module on Lampung ship ornaments can improve students' understanding with very good criteria. This shows that the Lampung ship ornament learning module can improve understanding and learning outcomes for vocational students.